2020
DOI: 10.1097/aud.0000000000000925
|View full text |Cite
|
Sign up to set email alerts
|

Bone Conduction Vibration Vestibular Evoked Myogenic Potential (VEMP) Testing: Reliability in Children, Adolescents, and Young Adults

Abstract: Objectives: Bone conduction vibration (BCV) vestibular evoked myogenic potentials (VEMP) are clinically desirable in children for multiple reasons. However, no accepted standard exists for stimulus type and the reliability of BCV devices has not been investigated in children. The objective of the current study was to determine which BCV VEMP method (B-71, impulse hammer, or Mini-shaker) yields the highest response rates and reliability in a group of adults, adolescents, and children. It was hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 43 publications
1
22
2
Order By: Relevance
“…Note that although the mean of the amplitude ratio is higher for males than females, but this difference falls within the 95% confidence limits. (12,13,22,23). In addition, the present study with a larger population provides more reliable values and better suited methods to the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that although the mean of the amplitude ratio is higher for males than females, but this difference falls within the 95% confidence limits. (12,13,22,23). In addition, the present study with a larger population provides more reliable values and better suited methods to the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in a population including children older than 5 years (n = 21) and adults (n = 9) c-VEMP amplitude was observed to decrease with age for BC but not AC (22). One study of 30 healthy children aged 3-11 years reported shorter AC c-VEMP latencies only in participants aged from 3 through 5 years (23).…”
Section: Introductionmentioning
confidence: 99%
“…VEMP test results can be confounded by even modest air-bone gaps (37,38). However, the recent introduction of VEMP testing delivered from bone conduction transducers can provide reliable results in such cases (39). Although routine utilization was low in this study (4.7%), we did find that 15.4% of practitioners with less than 5 years of experience used VEMP for preoperative assessment.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, this may contribute to the different stimulus modality. Studies have reported that the mechanisms of ACS and BCV to activate otolith organs are different ( 57 ). It seems that ACS predominantly activates saccular afferents, while BCV stimulates both saccular and utricular afferent ( 58 ).…”
Section: Discussionmentioning
confidence: 99%